Social Partnership: Rebuilding Union Capacity Through Education - Michael Law (Adult Education Research Conference, 2004)
This paper employs a case study approach in order to update an expand on previous analyses of developments in union education in New Zealand. This particular paper focuses on the role of union education in the rebuilding of union capacity and reflects on theoretical and practical difficulties that confront unions in the wake neoliberaism.